Advances in Indoor Positioning and Indoor Navigation - Antoni Perez-Navarro; Raúl Montoliu; Joaquín Torres-Sospedra (Sensors, 2022)
Locating devices in indoor environments has become a key issue for many emerging location-based applications and intelligent spaces in different fields [...]